2010
DOI: 10.1164/201001-0037oc
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic 2009 Influenza A in Argentina

Abstract: Patients with 2009 influenza A (H1N1) requiring mechanical ventilation were mostly middle-aged adults, often with comorbidities, and frequently developed severe acute respiratory distress syndrome and multiorgan failure requiring advanced organ support. Case fatality rate was accordingly high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
82
4
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(100 citation statements)
references
References 41 publications
12
82
4
2
Order By: Relevance
“…Differences with other studies might be related to our critically ill population, for whom the criteria were standardized on the basis of AKIN criteria. Finally, mortality rates of 16%, 19% and 54%, respectively, have been reported among critically ill patients with H1N1 virus infection in Brazil [33], Argentina [5] and Canada [3]. The main difference is that in the present study, although the mortality rate was 18.8% and significantly higher for patients who developed AKI, multivariate analysis demonstrated that only AKIN stage III was independently associated with ICU mortality.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Differences with other studies might be related to our critically ill population, for whom the criteria were standardized on the basis of AKIN criteria. Finally, mortality rates of 16%, 19% and 54%, respectively, have been reported among critically ill patients with H1N1 virus infection in Brazil [33], Argentina [5] and Canada [3]. The main difference is that in the present study, although the mortality rate was 18.8% and significantly higher for patients who developed AKI, multivariate analysis demonstrated that only AKIN stage III was independently associated with ICU mortality.…”
Section: Discussioncontrasting
confidence: 60%
“…However, the information regarding the incidence and impact of renal failure among these patients remains scarce. The World Health Organization (WHO) warned physicians that patients H1N1 virus infection might develop renal impairment ranging from just mild disease to the need for renal replacement therapy (RRT) [1-5]. …”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies of A/H1N1 reported that one of the most important risk factors for complications of severe illness with A/H1N1 infection were age [10,27-29]. In the current study, however, age was not a significant factor associated with rapid disease progression of A/H1N1 infection in children.…”
Section: Discussioncontrasting
confidence: 75%
“…In addition, immunosuppression was a main risk factor for early mortality among 337 Argentinean patients admitted to ICU with influenza like illness and respiratory failure that required mechanical ventilation. Mortality was highly associated with refractory hypoxemia 25 . These data explain our high mortality rate observed among the 17 patients who were admitted to ICU (11/17; 65%) or among the 12 patients who developed respiratory failure (11/12; 92%).…”
Section: Discussionmentioning
confidence: 99%